2001
DOI: 10.1523/jneurosci.21-20-j0003.2001
|View full text |Cite
|
Sign up to set email alerts
|

Motion-Induced Perceptual Extrapolation of Blurred Visual Targets

Abstract: In the motion-extrapolation hypothesis, the visual system can extrapolate the instantaneous position of a moving object from its past trajectory. The existence of such a mechanism in human vision has been intensely debated. Here, we show compelling perceptual extrapolation of both first- and second-order moving stimuli, the magnitude of which depends on blurring of the visual target. The spatiotemporal characteristics of the extrapolation can be quantitatively accounted for by a simple model based on temporall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 28 publications
12
77
1
Order By: Relevance
“…Previous studies by Fu et al (2001) and Kanai et al (2006) demonstrated that the extrapolation of visual targets farther in the direction of motion was larger for spatially blurred targets-that is, for targets with a high degree of position uncertainty. Our results at paralateral spatial locations are in accord with these earlier findings and confirm that position uncertainty due to less precise encoding of spatial coordinates leads to larger forward displacements.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies by Fu et al (2001) and Kanai et al (2006) demonstrated that the extrapolation of visual targets farther in the direction of motion was larger for spatially blurred targets-that is, for targets with a high degree of position uncertainty. Our results at paralateral spatial locations are in accord with these earlier findings and confirm that position uncertainty due to less precise encoding of spatial coordinates leads to larger forward displacements.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in which position uncertainty was induced either by the blurring of target intensity and contrast (Fu, Shen, & Dan, 2001) or by peripheral stimulus presentation (Kanai, Sheth, & Shimojo, 2006) have shown that less accurate positional information results in larger forward displacements. On the basis of the latter findings, we hypothesized that less precise encoding of spatial coordinates in paralateral and lateral space leads to greater position uncertainty and should be reflected in an increase in the magnitude of forward displacement.…”
mentioning
confidence: 99%
“…There is strong evidence that this occurs in perception (Ramachandran and Anstis 1990;De Valois and De Valois 1991;Snowden 1998;Nishida and Johnston 1999;Whitaker et al 1999;Hayes 2000;Whitney and Cavanagh 2000;Fu et al 2001;McGraw et al 2002;Mussap and Prins 2002;Edwards and Badcock 2003;Watanabe et al 2003;Whitney et al 2003a;Durant and Johnston 2004;Fu et al 2004;Shim and Cavanagh 2004; for a review, see Whitney 2002), and in visually-guided behavior (Mohrmann-Lendla and Fleischer 1991;Brenner and Smeets 1997;Yamagishi et al 2001;Ma-Wyatt and McGraw 2003;Whitney et al 2003b;Ashida 2004), though the influence of visual motion on perception and action may operate on different timescales (Whitney et al 2003b). This explanation is consistent with the finding that even during fixation, a moving background can influence reaching movements to a stationary object (Brenner and Smeets 1997;Yamagishi et al 2001;Whitney et al 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…Either the flash-lag is an ensemble of different phenomena -and some, indeed, are unusual 92 -that have their own explanations, or there is one explanation common to visual change in general. One could go one step further and ask: do changes in modalities other than vision produce similar illusions?…”
Section: Discussionmentioning
confidence: 99%